Trends in Auditor Reporting in Australia: A Synthesis and Opportunities for Research. Issue 3 (September 2016) - Carson, Elizabeth; Fargher, Neil; Zhang, Yuyu
Abstract : The purpose of this review is to synthesise the existing research literature regarding audit reporting and, in particular, the going concern decision. We consider the findings of research conducted in Australia and New Zealand on these issues. We then analyse trends in audit reporting from 2005 to 2013. We identify an increase in auditors' reports highlighting going concern issues well beyond the global financial crisis period confirming that this period represents a period of prolonged economic uncertainty. We identify trends by audit firm type, by industry and company size. We analyse the subsequent year outcomes for firms receiving going concern opinions. We also identify opportunities for future research.